The product manager's survival guide : everything you need to know to succeed as a product manager - Haines, Steven (McGraw-Hill, 2019)
Advance in your product management career and create innovative products that customers love! Regardless of industry or sector, to compete in today's business world, product managers must understand how their customer's preferences change, how technology evolves, and how anticipate what competitors might do. Regardless of industry, you need a reliable resource that provides timely guidance and practical tools to help you compete. With new content and expert advice, this updated edition of The Product Manager's Survival Guide brings you fully up to date on what you need to succeed as a product manager. For your professional future, you'll learn it's not the development technique that will help you get ahead, it's how you think like a strategically minded business person. Your continuous learning starts with your product management acumen assessment, and takes root, when you develop your own professional development strategy. The Product Manager's Survival Guide, Second Edition features brand new material, including: -A product management acumen assessment -Action planning ideas at the end of each chapter -Techniques to earn empowerment -Tools to develop product strategies and roadmaps -Methods to deploy and release products -Metrics to assess product performance Simple and easy to understand, this invaluable guide will help you bring your company into the digital age and continue to evolve with changing times.